Keadilan penilaian prestasi dalam kalangan guru dan hubungannya dengan motivasi kerja dan prestasi akademik sekolah - Shaari, Abdull Sukor; Yusof, Ab. Aziz; Jamal Khan, Mohd Khan; Tang, Swee Mei; Lim, Kong Teong (Universiti Utara Malaysia, 2008)
Purpose - This study investigated teachers’ perception on fairness of performance appraisal with respect to procedural justice and distributive justice. This study also explored the possible relationship between both aspects of justice and their impact on school achievement measured by teacher work motivation and school academic performance. Design/Methodology/Approach - The survey was carried out in 110 secondary schools selected randomly from a listing of secondary schools in Kedah and Perlis. The final number of participants for this study was 86 schools, with a response rate of 78%. Findings - Correlation analysis indicated that (a) procedural justice has significant positive correlation with distributive justice; (b) work motivation has significant positive correlation with distributive justice; and(c) school academic performance has significant positive correlation with both procedural and distributive justice. Furthermore, results of regression analysis also indicated that both aspects of justice have a significant positive relationship with work motivation and school academic performance. Originality/Value - Findings of this study demonstrated that fairness of performance appraisal could contribute to the effort of educational organisations in enhancing work motivation and academic performance. Paper type - Research Paper.